PENINGKATAN EFISIENSI PAKAN DAN PERFORMANS ITIK LOKAL MELALUI APLIKASI PROBIOTIK BAKTERI ASAM LAKTAT - Sri Sumarsih; C.I. Sutrisno; B. Sulistiyanto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2012)
Probiotics have a role in increasing the productivity of duck. The aim of the research was to evaluate the effect of Lactic Acid Bacteria (LAB) probiotics on feed efficiency and duck’s performance. The completely randomized design was been used on this research with 3 treaments and 5 replications. The treatments were R0 (feed with 0% LAB probiotics), R1 (feed with continuously LAB probiotics) and R2 (feed with LAB probiotics repeated at 1, 4, 28 and 42 days). Feed composed of iso crude protein (18%) and energy (2800 kkal/kg). The parameters were feed efficiency and duck’s performance (feed consumption and body weight gain). The results showed that the BAL probiotics significantly (p<0,05) increasing feed efficiency and body weight gain. The BAL probiotics significantly (p<0,05) decreasing feed consumption and feed conversion). The conclusion was Lactic Acid Bacteria (LAB) probiotics can be used to improve feed efficiency and duck’s performance.